Widespread suppression of intragenic transcription initiation by H-NS - Singh, Shivani S. (Cold Spring Harbor Laboratory Press, 2014)
Widespread intragenic transcription initiation has been observed in many species. Here we show that the Escherichia coli ehxCABD operon contains numerous intragenic promoters in both sense and antisense orientations. Transcription from these promoters is silenced by the histone-like nucleoid structuring (H-NS) protein. On a genome-wide scale, we show that 46% of H-NS-suppressed transcripts in E. coli are intragenic in origin. Furthermore, many intergenic promoters repressed by H-NS are for noncoding RNAs (ncRNAs). Thus, a major overlooked function of H-NS is to prevent transcription of spurious RNA. Our data provide a molecular description for the toxicity of horizontally acquired DNA and explain how this is counteracted by H-NS.